Geographic separation of domestic and wild strains of Toxoplasma gondii in French Guiana correlates with a monomorphic version of chromosome1a. - Asis Khan; Daniel Ajzenberg; Aurélien Mercier; Magalie Demar; Stéphane Simon; Marie Laure Dardé; Qiuling Wang; Shiv Kumar Verma; Benjamin M Rosenthal; Jitender P Dubey; L David Sibley (Public Library of Science (PLoS), 2014)
Previous studies have stressed the genetic divergence and high pathogenicity of strains of T. gondii from French Guiana. Although strains from coastal, human adapted environments (so called anthropized) resemble those found in other regions of the Caribbean, strains collected from inland jungle environment are genetically quite diverse. To better understand the composition of these distinct strain types, we undertook a more in depth analysis of T. gondii strains from French Guiana including profiling of chromosome 1a (Chr1a), which is often shared as a single monomorphic haplotype among lineages that are otherwise genetically distinct.Comparison of intron sequences from selectively neutral genes indicated that anthropized strains were most closely related to clonal type III strains from North America, although wider RFLP analysis revealed that they are natural hybrids. In contrast, strains isolated from the jungle were genetically very diverse. Remarkably, nearly all anthropized strains contained the monomorphic version of Chr1a while wild stains were extremely divergent. The presence of the monomorphic Chr1a strongly correlated with greater transmission in domestic cats, although there were several exceptions, indicating that other factors also contribute. Anthropized strains also varied in their virulence in laboratory mice, and this pattern could not be explained by the simple combination of previously identified virulence factors, indicating that other genetic determinants influence pathogenicity.Our studies underscore the marked genetic separation of anthropized and wild strains of T. gondii in French Guiana and provide additional evidence that the presence of Chr1a is associated with successful expansion of widely different lineages within diverse geographic areas. The predominance of Chr1a among strains in the anthropized environment suggests that it may confer an advantage for transmission in this environment, and thus potentially contribute to the spread of pathogenecity determinants.